2014
DOI: 10.1007/s10709-014-9770-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, prevalence and host specificity of avian malaria parasites across the breeding range of the migratory lark sparrow (Chondestes grammacus)

Abstract: The lark sparrow (Chondestes grammacus) is a ground-nesting passerine that breeds across much of the central North American steppe and sand barrens. Through genotyping and sequencing of avian malaria parasites we examined levels of malaria prevalence and determined the distribution of Haemoproteus and Plasmodium lineages across the breeding range of the lark sparrow. Analysis of 365 birds collected from five breeding locations revealed relatively high levels of malaria prevalence in adults (80 %) and juveniles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
1
7
1
1
Order By: Relevance
“…Previous studies of avian malaria within lark sparrow populations have revealed relatively high infection rates across its range. For example, our lab has detected greater than 80 % infection rates across populations of this species, which contrasts with estimates from other passerines, ranging from 11 % in the blue-winged warbler, Vermivora pinus, to 58 % in the yellow-breasted chat, Icteria virens (Ricklefs et al 2005;Swanson et al 2014). With a diversity of parasite strains causing such common infections, avian malaria may act as an important selection pressure on MHC diversity.…”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Previous studies of avian malaria within lark sparrow populations have revealed relatively high infection rates across its range. For example, our lab has detected greater than 80 % infection rates across populations of this species, which contrasts with estimates from other passerines, ranging from 11 % in the blue-winged warbler, Vermivora pinus, to 58 % in the yellow-breasted chat, Icteria virens (Ricklefs et al 2005;Swanson et al 2014). With a diversity of parasite strains causing such common infections, avian malaria may act as an important selection pressure on MHC diversity.…”
Section: Introductioncontrasting
confidence: 60%
“…The lark sparrow (Chondestes grammacus) represents a passerine species with documented populations of reduced size subjected to extensive pathogen pressures (Swanson et al 2014). While denser breeding populations exist mainly in the Central Plains of North America and California (Baepler 1968;Martin and Parrish 2000), the lark sparrow is classified as a state endangered bird in Ohio (Ohio Department of Natural Resources 2012) because of a declining breeding population over recent decades caused by decreases in suitable habitat (Martin and Parrish 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Their high diversity (at least 900 lineages, Bensch, Hellgren, & Pérez‐Tris, ) and their variability in virulence make them good candidates to investigate parasite‐mediated divergent selection. Haemosporidian parasites are also very common in many bird species (Ayadi et al., ; van Rooyen, Lalubin, Glaizot, & Christe, ; Swanson, Lyons, & Bouzat, ) and can reach high prevalence, for example in great tits ( Parus major ) where prevalence was as high as 91% in some Swiss populations (Glaizot et al., ). These parasites are represented by the genera Plasmodium , Haemoproteus , and Leucocytozoon and are transmitted by dipteran vectors (Valkiūnas, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bensch et al 2000;Waldenstöm et al 2004;Bensch and Å kesson 2003;Scheuerlein and Ricklefs 2004;Wood et al 2007;Jenkins and Owens 2011;Swanson et al 2014;Zhao et al 2014).…”
Section: Introductionunclassified